MORTGAGE LENDING PRACTICE IN COMMERCIAL BANKS - Otabek Olimovich Muslimov; Abrorjon Husanugli Azamov (Ecominds Press, 2025)
Mortgage lending is one of the fundamental pillars of commercial banking, providing individuals and businesses with access to homeownership and real estate investment. The development of mortgage lending in commercial banks is influenced by a range of economic, regulatory, and institutional factors. In Uzbekistan, mortgage lending has witnessed significant reforms, aimed at expanding financial accessibility and promoting economic growth. This paper examines the current practice of mortgage lending in commercial banks, analyzing the regulatory framework, financial mechanisms, and challenges associated with mortgage loans. The study also investigates the impact of mortgage lending on economic stability, the role of interest rates, and the strategies employed by commercial banks to manage credit risk. By exploring these aspects, the paper provides insights into the efficiency and sustainability of mortgage lending in Uzbekistan, identifying potential areas for policy improvement and financial innovation.
Keywords: Mortgage lending, commercial banks, credit risk, financial stability, interest rates, housing market, economic growth, regulatory framework, financial accessibility.